Usefulness of the obturator hook technique for guiding the initial trajectory control in infra-acetabular screw placement. (28th February 2021) - Lim, Eic Ju; Sakong, Seungyeob; Son, Whee Sung; Kim, HanJu; Cho, Jae-Woo; Oh, Jong-Keon
Purpose: Proper placement of infra-acetabular screws is technically demanding; there is a limited safe zone for screw fixation because of the complexity of the bone anatomy around the hip joint and the vulnerability of the major neurovascular bundles in the pelvic cavity. We aimed to present the obturator hook technique as a surgical technique for infra-acetabular screw placement in acetabular and pelvic fractures and report its radiological outcomes. Methods: Patients treated with infra-acetabular screw placement using the obturator hook technique between January 2015 and August 2020 were enrolled in this study. We collected data on demographics, surgical approach, reduction status, complications, and outcomes. The radiological outcomes of infra-acetabular screw placement based on computed tomography findings were evaluated as follows: success, articular penetration, or out of the bone. Results: Thirty-five patients underwent infra-acetabular screw placement (26 men, 9 women; mean age, 55 years; range, 27–90 years). One patient underwent bilateral infra-acetabular screw placement; therefore, 36 infra-acetabular screws were inserted in all patients. An ideal placement was achieved with 27 infra-acetabular screws (27/36, 75%). Seven infra-acetabular screws (7/36, 19%) showed articular penetration, and two infra-acetabular screws (2/36, 6%) were placed outside the bone. One patient with articular penetration and mechanical symptoms of the hip joint required screw replacement. No other complications, including obturator nerve and vascular injuries, were observed. Conclusion: The obturator hook technique could be a favorable and individualized method for infra-acetabular screw placement in patients with acetabular and pelvic fractures. Level of Evidence: IV, retrospective descriptive study.